Review of the biodiversity and limno-ecological studies on Lake Taal updates from the last 10 years - de Leon, Justine R. (Philippine Journal of Science, 2023)
Lake Taal is one of the most significant lake ecosystems in tropical East Asia. In 2011, a review paper consolidated all known biodiversity and limno-ecological studies conducted in Lake Taal from the beginning of the 20th century all the way to the late 2000s. It highlighted that insufficient funding, inadequate long-term monitoring data, and the publication culture of that time impeded having a comprehensive understanding of the lake. Since then, much research work has been done in Lake Taal, especially during the past decade. This review paper provides an analysis and summary of the research work conducted in Lake Taal over the past 10 years. The recent decade has seen a steady increase in scientific interest in Lake Taal made evident by more scientists and institutions working on topics involving the lake. Research grants, collaborations, and publications have also significantly increased during the past 10 years. This has led to an improved understanding of the lake’s biodiversity, ecology, and impacts of intensive aquaculture and the introduction of non-native species. Taken together, this paper presents a better understanding of Lake Taal, which can be utilized for the design and improvement of conservation, preservation, and management programs for this multi-use freshwater system.